EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KEDISIPLINAN SISWA KELAS VIII A DI SMP NEGERI 14 BANJARMASIN - Astuti, Sri; Hamzah, Hamzah; Heiriyah, Ainun (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2018)
ABSTRACT This study is based on preliminary observations at SMP Negeri 14 Banjarmasin, there are students in schools who do not apply the discipline attitude in the school environment. It was known from students who arrived late at school, dressed not according to the rules, did not go to school without information, went out during class hours, chatting with friends during class hours, neglecting schoolwork and this was often complained by other subject teachers. The formulation of the problem in this study is how much the level of discipline of students before or after being given services and whether group guidance services with role playing techniques are influential to reduce students who lack discipline. This study aims to find out how much the level of discipline of students before and after being given services and knowing group guidance services with role playing techniques can have an effect on improving student discipline. This research method uses quantitative pre-experiment. The population in this study was class VIIIA with a total of 33 students. The results of student discipline before the group guidance service with role playing techniques from the initial test (O1) and the final test (O2) are said to increase student discipline because the value of posttest is higher than the pretest. Thus the researchers concluded that group guidance services were effective in increasing the discipline of class VIIIA students in SMP Negeri 14 Banjarmasin. Keywords: Group Guidance, Role Playing Techniques, Discipline